What is an appropriate educational response to controversial historical monuments?. Issue 3 (12th May 2021) - Merry, Michael S.; Schinkel, Anders
Abstract: There are many things that can be done to educate young people about historical monuments in schools. At the same time, however, we argue that there is little warrant for optimism concerning the educational potential of classroom instruction given the institutional constraints under which school teachers must labour. For these reasons, we think it best to expand the scope of educational possibilities one is willing to consider.